Awareness and perception of intra-abdominal adhesions and related consequences: survey of gynaecologists in German hospitals - Hackethal, Andreas; Sick, C.; Brüggmann, Dörthe; Tchartchian, Garri; Wallwiener, Markus; Münstedt, Karsten; Tinneberg, Hans-Rudolf (European journal of obstetrics & gynecology and reproductive biology)
Objective - Intra-abdominal adhesion formation after abdominal surgery is the most common postsurgical complication, and the consequences are a considerable burden for patients, surgeons and health systems. Since a wide variety of factors influence adhesion formation, it is difficult to define clear guidelines on how to reduce adhesion formation in daily practice. Given this dilemma, this study assessed the awareness and perception of adhesion formation among gynaecologists in Germany in order to define a baseline for further research and education. - Study design - The Clinical Adhesion Research and Evaluation (CARE) group of the University of Giessen designed a questionnaire that was sent to the heads of all gynaecological departments in Germany. The director or one of the surgical consultants was asked to complete the questionnaire and return it for evaluation. - Results - The completed questionnaire was returned by 279 of 833 gynaecological departments. Interviewed surgeons expected adhesions to form in 15% of cases after laparoscopy and 40% after laparotomy. Before surgery, 83.1% of the respondents told their patients about the risk of prior adhesion formation. More than 60% believed that postsurgical adhesion accounts for major morbidity. Infections within the abdomen, previous surgery and extensive tissue trauma were thought to have the most influence on adhesion formation. Risk of adhesion formation was thought to be highest in endometriosis and adhesiolysis surgery. The respondents agreed on performing adhesiolysis in symptomatic but not in all patients. Only 38.4% used adhesion reduction agents regularly. A total of 65.1% of a repertoire of adhesion prevention agents were familiar to the interviewed surgeons. Only 22.0% of them used anti-adhesion products in clinical practice. In general, the respondents were uncertain whether these products play an important role in adhesion reduction, represented by a range of 1.97±0.98% on a scale from 0 to 4. - Conclusions - Even though postoperative adhesions are recognized as a major cause for morbidity, and it is widely agreed that infections, extensive tissue trauma and surgery lead to adhesion formation, there is uncertainty about the treatment and prophylactic strategies for dealing with adhesions. This dilemma reflects the awareness and perception of gynaecologists in Germany and is an initial point for further research.
Gesehen am 13.06.2023